2013
DOI: 10.1177/1721727x1301100131
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin Therapy When Plasmapheresis Fails in Thrombotic Thrombocytopenic Purpura Associated with Severe ADAMTS 13 Deficiency in Childhood: A Case Report

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a disorder of the blood-coagulation system, causing extensive microscopic clots to form in the small blood vessels throughout the body. TTP is quite a rare pathology in childhood, being more frequent among adults. Often it is hardly to distinguish from other haematological pathologies in children both for its uncommon incidence and for the presence of clinical forms that are heterogeneous and difficult to classify. We report the case of an ll-year-old girl suffering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the latter a study of metallo-protease ADAMST 13 showed a low value (<10%) with positive anti-ADAMTS 13 IgG and inhibitor, strengthening the hypothesis of an autoimmune process. 73 In addition, Corticosteroids have been widely used in infantile spasms and West Syndrome, and there is still a debate on their efficacy when compared with the historical used Vigabatrin therapy 74 On the basis of the large involvement of IL-1beta in immunemediated epileptogenesis, the compounds showing greatest promise belong to the group of inhibitors known as interleukin converting enzyme (ICE)/caspase-1, the proteases that catalyzes the conversion of the inactive precursor pro-IL-1beta to active IL-1beta. 75 This kind of inhibitor acts to reduce the release of IL-1beta in organotypic hippocampal slices following exposure to pro-inflammatory stimuli, 76 decreasing acute seizure activity following intra-hippocampal kainate in rats, 76 and restricts the generalization of seizures in a rapid kindling model.…”
Section: Immunotherapeutic Strategy In Epilepsy-a Focus On Inflammationmentioning
confidence: 99%
“…In the latter a study of metallo-protease ADAMST 13 showed a low value (<10%) with positive anti-ADAMTS 13 IgG and inhibitor, strengthening the hypothesis of an autoimmune process. 73 In addition, Corticosteroids have been widely used in infantile spasms and West Syndrome, and there is still a debate on their efficacy when compared with the historical used Vigabatrin therapy 74 On the basis of the large involvement of IL-1beta in immunemediated epileptogenesis, the compounds showing greatest promise belong to the group of inhibitors known as interleukin converting enzyme (ICE)/caspase-1, the proteases that catalyzes the conversion of the inactive precursor pro-IL-1beta to active IL-1beta. 75 This kind of inhibitor acts to reduce the release of IL-1beta in organotypic hippocampal slices following exposure to pro-inflammatory stimuli, 76 decreasing acute seizure activity following intra-hippocampal kainate in rats, 76 and restricts the generalization of seizures in a rapid kindling model.…”
Section: Immunotherapeutic Strategy In Epilepsy-a Focus On Inflammationmentioning
confidence: 99%